Matematično modeliranje prirasta kosmov v biokemijskih reaktorjih - Panjan, Jože (Acta hydrotechnica, 1999)
The purpose of the biochemical reactor, in which an accelerated natural self-purification is carried out, is to covert dissolved and insoluble substances into a settleable form. This process is enabled by microorganisms which constitute a part of the dispersed biomass in the water of the biochemical reactor. Wastewater should satisfy the minimum conditions for the growth of microorganisms. Organisms in the activated sludge take over organic and partially inorganic compounds and transform them into new organisms which form flocks of the activated sludge in the secondary treatment basin. Processes of the growth of flocks can be evaluated experimentally or by mathematical models. Diffusion equations for glucose and oxygen into flocks are applied. Mathematical models for spherical, cylindrical and disklike flocks, the equation for shearing forces which determine the maximal dimensions of flocks in the reactor and the stability equation will be demonstrated
Keywords: biological reactor; biološki reaktorji; blato; flocks; kosmi; matematični modeli; mathematical model; microorganisms; mikroorganizmi; sludge